The role of Circle women in curbing violence against women and girls in Africa - Owusu-Ansah, Sylvia (Verbum et ecclesia, 2016)
The article looks at the role Circle of Concerned African Women Theologians (the Circle) have played in the struggle to end or reduce the rate at which violence against women and girls occurs in West Africa by highlighting the contributions of older Circle women, especially the initiator of the Circle, Mercy Amba Oduyoye. The initiator of the Circle and other older Circle women have left a remarkable legacy that needs to continue by the current and future generations of the Circle. The background information examines the leadership and mentorship of Mercy Amba Oduyoye and the impact she has made in the lives of African women. The essay then looks at the types of violence that women face in West Africa with the specific contributions of Circle women in the struggle to end violence against women and girls. It then argues that Circle women have played very significant roles both in setting the pace and giving the platform for women activities to minimise gender-based violence against women and girls. Circle women have written and presented papers that have addressed many challenges including HIV and/or AIDS, Girl Child trafficking, Marriage of Minors, and almost all kinds of violence against women and girls. Currently, religious violence threatens the fabric of African nations causing insecurity and panic, women and girls being the most vulnerable. The challenge to the present and future Circle members is to contribute in significant ways towards religious harmony in Africa and beyond. The Circle acknowledges the leadership role of women and encourages them to spearhead the liberation of women as well as empower them to be able to aspire to get to the top or become independent. No one understands what someone else feels better than the person experiencing the ordeal. Women can better understand what they go through and also have the passion to strive towards liberation.Intradisciplinary and/or interdisciplinary implications: In this article, the discipline of practical theology combines with elements of social science and Gender Studies, bringing out the Circle's contribution towards the eradication of religious and cultural and gender violence against women and girls in Ghana and Africa.Keywords: Circle; Theology; gender-based violence; Mercy Amba Oduyoye; West Africa